PENGARUH SANKSI PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI MANADO - Siamena, Elfin; Sabijono, Harijanto; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2017)
The number of taxpayers from year to year increases. But the increase in the number of taxpayers is not offset by taxpayer compliance in paying taxes. The compliance issue becomes an obstacle in maximizing tax revenues. This study aims to analyze the effect of tax sanctions and taxpayer awareness on the compliance of individual taxpayers. The population of this study is determined based on purposive sampling method, the data collected by division of questionnaires in KPP Pratama Manado. The method of research analysis used is multiple linear regression. based on the result of t test, it can be concluded that the tax sanction has positive and significant effect on the taxpayer compliance of the individual, with the value of significance smaller than the significant value (0.001 < 0.05), the consciousness of the taxpayer positively and significantly influence the compliance personal taxpayer, this is indicated by a value of significance smaller than the significant value (0.003 < 0.05).Keywords :Tax sanctions, Taxpayer awareness, Personal taxpayer compliance